Analisis Variabilitas Gelombang Swell di Perairan Menui, Kecamatan Menui Kepulauan, Kabupaten Morowali, Provinsi Sulawesi Tengah - Borjus, Borjus; Irawati, Irawati; Pratikino, Asrin Ginong (Dept. Marine Science, 2026)
This study analyzes the characteristics and variability of swell waves in the Menui Waters, Morowali Regency, during the 2015–2024 period using ECMWF data. The analysis was conducted through statistical methods, spatial mapping, and Python-based data visualization. The results indicate that swell dynamics in the study area are primarily controlled by the southeast monsoon (June–August), while the contribution of tropical cyclones is relatively minor. Period distribution shows dominance of short-period wind waves (71.1%) and moderate-period swell (28.8%), with the latter exhibiting an average wave height of 0.74 m, approximately 2.6 times higher than wind waves, whereas long-period swell rarely develops due to the semi-enclosed basin characteristics. An increasing trend in wave height observed in several years, particularly in 2015, 2019, and 2024, suggests the influence of climate variability and change.